Tracing the lines: Scottish Grooved Ware trajectories beyond Orkney - Copper, Mike; Hamilton, Derek; Gibson, Alex (Proceedings of the Society of Antiquaries of Scotland, 2021)
This article presents the results of the recent Historic Environment Scotland-funded project Tracing the Lines: Uncovering Grooved Ware Trajectories in Neolithic Scotland addressing the timing and nature of the adoption, development and ultimate demise of Grooved Ware in Scotland beyond Orkney. Following analysis within a Bayesian framework of over a hundred Grooved Ware-associated radiocarbon dates from Scotland beyond Orkney, evidence is presented that Grooved Ware pottery very closely related to Orcadian prototypes began spreading rapidly between key locales across Scotland towards the end of the 4th millennium BC. This was followed by a process of stylistic drift with regional variations. The so-called Durrington Walls sub-style was introduced some 200 years after the earliest Grooved Ware and is an exception to this pattern of gradual change. Our modelling suggests that the latest Scottish Grooved Ware has a currency that overlaps with the earliest Beakers by between 1 and 145 years and probably between 1 and 60 years.